Kalachakra tsam and Dokshitov tsam in Buryatia: Contemporary Adaptations and Interpretations - Aiakova, Zhargal A. (The New Research of Tuva, 2025)
The article analyzes two types of the Tibetan tsam tradition: the Kalachakra tsam and the Dokshitov tsam, which were revived and are practiced in Buryatia after a long interruption during the Soviet era. The study considers the features of their modern adaptations and methods of worldview interpretation. The main materials for analysis were ceremonies observed and studied by the author: the Kalachakra tsam at the Duinhor datsan in Ulan-Ude in April 2024, and the Dokshitov tsam at the Sartuul-Bulak datsan in the Dzhida district in September 2024. The author also drew on Buddhist treatises, Buddhist scholarship, and other sources.The foundation for examining these mysteries lies in the fact that the revival of the tsam tradition in post-Soviet Buryatia was carried out under the guidance of Tibetan teachers and in accordance with canonical standards. To train and prepare monks, a tantric faculty was established at the Buddhist University “Dashi Choinkhorlin”, and the Duinhor (Kalachakra) datsan was erected specifically for both study and the practice of teachings and performance of the tsam ritual.The research demonstrates that the Kalachakra tsam and Dokshitov tsam, while maintaining their worldview foundations, are being adapted to contemporary conditions, facilitating understanding of Buddhist doctrine, its transmission, and initiations, as well as strengthening the foundations of Buddhist religious teaching. The tsam tradition, as an important element of Buddhist practice, undoubtedly makes a significant contribution to the formation of Buddhist worldview, revealing key ideas about emptiness and compassion, karma, and rebirth.
Keywords: Buddhism; Mahayana; Vajrayana; Gelug; Kalachakra tsam; Dokshitov tsam; Duinhor datsan; Buryatia